Does severe soil drought have after-effects on arbuscular and ectomycorrhizal root colonisation and plant nutrition? - Kilpeläinen, Jouni; Barbero-López, Aitor; Vestberg, Mauritz; Heiskanen, Juha; Lehto, Tarja (Springer, 2017)
Background and aims Arbuscular (AM) and ectomycorrhizas (EM) predominate in different soils. We hypothesise that also climatic factors affect directly their relative success and AM fungi (AMF) generally tolerate drought better than EM fungi (EMF). Here we tested the colonisation rates of soil-borne AMF and EMF after soil drought treatments. Methods Forest and meadow soils were mixed to include AMF and EMF propagules. There were three soil treatments: soil moisture corresponding to 60% (control) or 10% in mass of maximum water retention, or air-dry. The bait plants were EM-forming silver birch (Betula pendula), dual-mycorrhiza forming grey alder (Alnus incana) and AM-forming white clover (Trifolium repens). After re-watering, bait plants were sown and grown in a growth chamber in favourable conditions. This way, hostplant responses to drought were eliminated. Results Previous soil drought decreased EM colonisation in alder. The spore formation by AMF in clover was negatively affected after the most severe soil drought treatment, suggesting slightly retarded AM formation. Soluble soil potassium concentrations were lower in drought-treated soils and this was reflected in birch foliar concentrations. Conclusions The results provide some support to the hypothesised better drought tolerance of AMF than EMF propagules but further studies in milder drought and in other plant-fungus combinations are needed.
Keywords: dual mycorrhiza; Ectomycorrhiza; soil moisture; Arbuscular mycorrhiza; drought; Ectomycorrhizae; nutrients; soil water content